The Effectiveness Of Mr Dhanis’s Video On Instagram Toward Students’ Vocabulary Mastery - Evafaliyanti Evafaliyanti; Usmawita Usmawita (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2019)
Vocabulary is the central of the language and critical important that must be mastered by the students. However, most of the students just know the common vocabulary that they usually used. The use of Mr. Dhanis’s video on Instagram is believed to be able to increase the student’s vocabulary mastery. The aim of this research is to find out the effectiveness of Mr. Dhanis’s video on Instagram toward students’ vocabulary mastery. This research uses quantitave research and experiment method. The population of the research consist of 142 students at the eleventh grade students in SMA N 01 Metro. The researcher takes 62 students as the sample, then divided the students into two group, 31 students as the experiment class and 31 students as the control class. The researcher uses cluster random technique and uses t-test formula. The instruments of this research are pre-test and post-test. The result of the first hypothesis indicated that the value of t obtained (13.590) was higher than that of t table (2.042) at the significance level 0.05 and the significance (0.000) was lower than 0.05. Because of this the hypothesis is accepted. Then, the second hypothesis indicated that the value of t obtained (12.242) was higher than t table (2.042). That is why, the second alternative hypothesis (Ha) is accepted. It means that teaching vocabulary using Mr. Dhanis’s video on Instagram at the eleventh grade students of SMA Negeri 1 Metro is effective to increase vocabulary mastery and to give a significant difference on English vocabulary mastery.